Can pain and function be distinguished in the Oxford Hip Score in a meaningful way?: an exploratory and confirmatory factor analysis. Issue 11 (November 2014) - Harris, K. K.; Price, A. J.; Beard, D. J.; Fitzpatrick, R.; Jenkinson, C.; Dawson, J.
Abstract : Objective: The objective of this study was to explore dimensionality of the Oxford Hip Score (OHS) and examine whether self-reported pain and functioning can be distinguished in the form of subscales. Methods: This was a secondary data analysis of the UK NHS hospital episode statistics/patient-reported outcome measures dataset containing pre-operative OHS scores on 97 487 patients who were undergoing hip replacement surgery. Results: The proposed number of factors to extract depended on the method of extraction employed. Velicer's Minimum Average Partial test and the Parallel Analysis suggested one factor, the Cattell's scree test and Kaiser-over-1 rule suggested two factors. Exploratory factor analysis demonstrated that the two-factor OHS had most of the items saliently loading either of the two factors. These factors were named 'Pain' and 'Function' and their respective subscales were created. There was some cross-loading of items: 8 (pain on standing up from a chair) and 11 (pain during work). These items were assigned to the 'Pain' subscale. The final 'Pain' subscale consisted of items 1, 8, 9, 10, 11 and 12. The 'Function' subscale consisted of items 2, 3, 4, 5, 6 and 7, with the recommended scoring of the subscales being from 0 (worst) to 100 (best). Cronbach's alpha was 0.855 for the 'Pain' subscale and 0.861 for the 'Function' subscale. A confirmatory factor analysis demonstrated that the two-factor model of the OHS had a better fit. However, none of the one-factor or two-factor models was rejected. Conclusion: Factor analyses demonstrated that, in addition to current usage as a single summary scale, separate information on pain and self-reported function can be extracted from the OHS in a meaningful way in the form of subscales. Cite this article: Bone Joint Res 2014;3:305–9.